SYSTEM FOR PRESSURISED IRRIGATION FROM A TRAILER WITH A MODULE FOR GENERATING PHOTOVOLTAIC ENERGY - GARCÍA PÉREZ, JULIAN (2015)
The invention consists of a four-wheeled trailer on the platform of which there is a rotary base which supports at least four assemblies each consisting of five double plates, said assemblies being folded vertically, with a space between each one in a transport situation, without going beyond the dimensions of said platform, a high-pressure irrigation pump supplied with photovoltaic energy being arranged in the front part of said trailer, the activation of which is controlled by an intelligent control module and said plates can be opened up into a working position. Constituido a partir de un remolque de cuatro ruedas sobre cuya plataforma se encuentra una base giratoria que sustenta al menos cuatro conjuntos de cinco placas dobles cada uno, plegados en vertical y con un vano entre cada conjunto en situación de transporte, sin rebasar las dimensiones de dicha plataforma, hallándose en la parte delantera de dicho remolque una bomba de riego de alta presión alimentada con energía fotovoltaica cuya activación es controlada por un módulo inteligente de control y pudiéndose desplegar dichas placas en posición de trabajo. Le système selon la présente invention est constitué à partir d'une remorque à quatre roues sur la plateforme de laquelle se trouve une base tournante qui soutient au moins quatre ensembles de cinq plaques doubles chacun, pliés à la verticale et présentant un espacement entre chaque ensemble en situation de transport, sans dépasser les dimensions de ladite plateforme, la partie avant de ladite remorque logeant une pompe d'irrigation à haute pression alimentée par l'énergie photovoltaïque dont l'activation est commandée par un module intelligent de commande et lesdites plaques pouvant se déplier en position d'utilisation.